Co-assembly of liposomes, Dendrimersomes, and Polymersomes with amphiphilic Janus dendrimers conjugated to Mono- and Tris-Nitrilotriacetic Acid (NTA, TrisNTA) enhances protein recruitment. (March 2022) - Xiao, Qi; Rivera-Martinez, Naomi; Raab, Calvin J.; Bermudez, Jessica G.; Good, Matthew C.; Klein, Michael L.; Percec, Virgil
Highlights: Two libraries of Janus dendrimers containing NTA and TrisNTA were synthesized. Janus dendrimer-NTA and TrisNTA are stable indefinitely at room temperature. Enhanced his-tagged protein requitement on the hybrid vesicles was demonstrated. These Janus dendrimers co-assemble with liposomes, dendrimersomes, and polymersomes. ABSTRACT: Metal-chelating ligands such as nitrilotriacetic acid (NTA) bind to polyhistidine-tagged (His-tagged) proteins. Lipids conjugated to NTA are widely used to decorate the surface of liposomes with proteins in cell biology applications. Multivalent NTA ligands such as tris-nitrilotriacetic acid (TrisNTA) display higher affinities than the monovalent NTA when co-assembled with phospholipids and cholesterol in liposomes. However, there is a limited number of available lipids conjugated to NTA and only few are commercially available. Additionally, their activity diminishes during storage or upon exposure to air. Here we report a library of five amphiphilic Janus dendrimers conjugated to NTA (JD-NTA) and three to TrisNTA (JD-TrisNTA). Both JD-NTA and JD-TrisNTA are indefinitely stable at room temperature in air and preliminary results demonstrate that they co-assemble with phospholipids and cholesterol into liposomes, with Janus dendrimers into dendrimersomes, and with block copolymers into polymersomes. The resulting hybrid liposomes co-assembled with JD-NTA display up to thirty-fold higher activity towards His-tagged fluorescent proteins when compared to lipid-NTAs. Hybrid liposomes co-assembled with JD-TrisNTA exhibit even higher binding affinity to His-tagged proteins and can function at much lower ligand concentration in hybrid liposomes than those containing JD-NTA. These preliminary results demonstrate the power of modular synthesis of JD-NTA or JD-TrisNTA to provide highly efficient new tools for biological reconstitution and synthetic cell biology as well as for nanomedicine. Graphical abstract: Image, graphical abstract